2014
DOI: 10.1017/s1474747214000043
|View full text |Cite
|
Sign up to set email alerts
|

Do 401k plan advisors take their own advice?

Abstract: Sponsors of defined contribution plans often hire financial advisors to help them to design and monitor these plans. I compare the designs of plans that advisors help create and monitor (client plans) to the designs of plans that the advisors use themselves (advisor plans). I find that advisors have an impact on the investment menus of their clients. Compared to an average pair of plans, a pair of plans that have the same advisor is more likely to hold identical funds and use identical fund families. Client pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Cheng, Raina, and Xiong (2014) find that midlevel managers in securitized finance personally invested in real estate during the mid-2000s housing boom. Dvorak (2015) shows that consultants typically design similar 401(k) plans for clients as they offer to their own employees, and Dvorak and Norbu (2013) show that employees of mutual fund companies invest their 401(k) plans disproportionately into their own firm's expensive, actively managed funds. Levitt and Syverson (2008), in contrast, find that real estate agents leave their own homes on the market longer and sell them at higher prices than their clients' homes.…”
mentioning
confidence: 99%
“…Cheng, Raina, and Xiong (2014) find that midlevel managers in securitized finance personally invested in real estate during the mid-2000s housing boom. Dvorak (2015) shows that consultants typically design similar 401(k) plans for clients as they offer to their own employees, and Dvorak and Norbu (2013) show that employees of mutual fund companies invest their 401(k) plans disproportionately into their own firm's expensive, actively managed funds. Levitt and Syverson (2008), in contrast, find that real estate agents leave their own homes on the market longer and sell them at higher prices than their clients' homes.…”
mentioning
confidence: 99%
“…In a similar spirit, Chetty, Looney, and Kroft (2009) discuss the impact of the salience of commodity taxes on consumer demand;Figlio and Lucas (2016) examine whether publicly disseminating information on school quality affects the real estate market in the area; andDranove et al (2003) ask how health outcomes change after the introduction of hospital report cards. See DellaVigna (2009) for a review.3 See for example, Del Guercio and Tkac (2008),Duarte and Hastings (2012),Kaniel and Parham (2017),Shaton (2017),Gao and Huang (2017),Da et al (2018),Evans andSun (2018), andBen-David et al (2019)) 4 Several other papers have identified inefficiencies in the structure of DC plans retirement: Huberman and Jiang (2006),Elton, Gruber, and Blake (2006), Brown, Liang, and Weisbenner (2007), Carroll et al (2009,Tang et al (2010), Chalmers, Johnson, andReuter (2013),Goldreich andHalaburda (2013), andDvorak (2015).…”
mentioning
confidence: 99%
“…In a similar spirit,Chetty, Looney, and Kroft (2009) discuss the impact of the salience of commodity taxes on consumer demand;Figlio and Lucas (2016) examine whether publicly disseminating information on school quality affects the real estate market in the area; andDranove et al (2003) ask how health outcomes change after the introduction of hospital report cards. See DellaVigna (2009) for a review.3 See for example, Del Guercio and Tkac (2008),Duarte and Hastings (2012),Kaniel and Parham (2017),Shaton (2017),Gao and Huang (2017),Da et al (2018),Evans andSun (2018), andBen-David et al (2019)) 4 Several other papers have identified inefficiencies in the structure of DC plans retirement:Huberman and Jiang (2006), Blake (2006, 2007),Brown, Liang, and Weisbenner (2007), Carroll et al (2009,Tang et al (2010), Chalmers, Johnson, andReuter (2013),Goldreich andHalaburda (2013), andDvorak (2015).…”
mentioning
confidence: 99%